Analyzing Thrifting Legality and Tax Compliance Through a Social Science Education Perspective - Mohammad Ilham Prasetyo; Evan Novika Ramdhani (Journal of Smart Pedagogy and Education, 2025)
The resurgence of illegal thrifting in Indonesia persists despite strict prohibitions under Minister of Trade Regulation Number 40 of 2022, creating a conflict between market demand and state sovereignty. This study analyzes the intersection of trade legality, tax compliance, and educational intervention using normative juridical and socio-pedagogical methods. Findings indicate that aggressive enforcement fails to address the root cause: irrational consumer behavior. Although traders seek legitimacy through tax payments, the government maintains that fiscal compliance cannot validate prohibited imports. Structural Equation Modeling reveals that "Trust in Government" significantly outweighs tax knowledge as a compliance predictor. Consequently, this research argues for a strategic shift toward integrating Social Science Education (IPS) and Project-Based Learning. Cultivating economic literacy and legal consciousness within the curriculum serves as the ultimate sustainable solution to curb illegal consumption, ensuring a transition from repressive short-term measures to long-term national economic resilience.